OGLE-2016-BLG-1195Lb: a sub-neptune beyond the snow line of an M-dwarf confirmed by Keck adaptive optics - Vandorou, Aikaterini; Dang, Lisa; Bennett, David P.; Koshimoto, Naoki; Terry, Sean K.; Udalski, Andrzej; Beaulieu, Jean-Philippe; Alard, Christophe; Bhattacharya, Aparna; Blackman, Joshua W.; Bond, Ian A.; Bouchoutrouch-Ku, Tarik; et al. (The astronomical journal, 2025)
We present the analysis of high-resolution follow-up observations of OGLE-2016-BLG-1195 using Laser Guide Star Adaptive Optics with Keck, seven years after the event’s peak. We resolve the lens, measuring its flux and the relative source-lens proper motion, thus finding the system to be a Mp = 10.08 ± 1.18M⊕ planet orbiting an M-dwarf, ML = 0.62 ± 0.05M⊙, beyond the snow line, with a projected separation of r⊥ = 2.24 ± 0.21 au at DL = 7.45 ± 0.55 kpc. Our results are consistent with the discovery paper, which reports values with 1σ uncertainties based on a single mass-distance constraint from finite source effects. However, both the discovery paper and our follow-up results disagree with the analysis of a different group that also present the planetary signal detection. The latter utilizes Spitzer photometry to measure a parallax signal claiming the system is an Earth-mass planet orbiting an ultracool dwarf. Their parallax signal though is improbable since it suggests a lens star in the disk moving perpendicular to or counter to the Galactic disk rotation. Moreover, microlensing parallaxes can be impacted by systematic errors in the photometry. Therefore, we reanalyze the Spitzer photometry using a pixel level decorrelation model to detrend detector systematics. We find that we cannot confidently recover the same detrended light curve that is likely dominated by systematic errors in the photometric data. The results of this paper act as a cautionary tale that a careful understanding of detector systematics and how they influence astrophysical constraints is crucial.